# Basic notation in lambda calculus

I have started learning lambda calculus from the book by Hindley and Seldin.

It brought up the concept with the function $x-y$, first as a function of $x$ and then as a function of $y$. In a way, it emphasized the difference between treating the expression as a function of $x$ and function of $y$, giving separate names to the functions.

$$f(x,y) = x-y \qquad\text{and}\qquad g(y,x) = x -y$$ and, in $\lambda$ notion, $$h = \lambda xy.x-y \qquad\text{and}\qquad g = \lambda yx. x-y\,.$$

If I am not wrong then it can be inferred that $f =\lambda x .(x-y)$ means that while computing the value of the expression the expression will vary only with $x$ and similarly when $\lambda$ is placed with $x$ the other variable $y$ will be kept as a constant.

But then it said that this can be denoted as, with $h$ being the common name of the function $$h = \lambda xy.(x-y)\qquad\text{and}\qquad h = \lambda yx.(x-y)\,.$$
Is it so that in the above expression the variable which is adjacent to $\lambda$ receives the value and the other one is constant? The above function is called a two-place function; what does that mean?

Then he introduces the following function in $\lambda$ notation calling it a one-point function: $$h^\star = \lambda x .(\lambda y . x−y)$$ and says that, for each number $a$, we have $h^\star(a)=\lambda y . a−y$. Here $a$ is being provided as an argument but $\lambda$ is placed near $y$. Why is this?

And then it deduces that $(h^\star(a))(b)=(\lambda y . a−y)(b) = a−b = h(a,b)$ and says $h^\star$ can be viewed as "representing" $h$. Is "representing" a technical term? How was $(\lambda y . a−y)(b) = a−b$ concluded?

If I am not wrong then it can be inferred that :

$f=\lambda x.(x−y)$ means that while computing the value of the expression the expression will vary only with "x" and similarly when "lambda " is placed with x the other variable y" will be kept as a constant .

Yes, intuitively that's how it works.

What you're looking is called Currying and it's explained fairly early in this book (in fact, I think it's the next section but I don't have a copy now to check). So when we want to work with functions with many arguments we often do it like this:

$$f(x,y,z) = x\times y + z$$

But you can break this into simpler functions, $(x \times y)$ and $(+z)$. The multiplication can be broken into even simpler terms, first I provide $x$, then just multiply by $y$, that is, $f^{\star}(y) = x\times y$.

Defining some 1-argument functions:

\begin{align*} plus_z &:= f^\prime(s) = s + z\\ times_y &:= f^\star(s) = s\times y \end{align*}

Combining these we can rewrite $f$ as:

$$f(x,y,z) = f^\prime(f^\star(x)) = plus_z (times_y ~ x)$$

Writing this in using $\lambda$ we have:

$$\lambda x y z. (x\times y + z) \equiv \lambda x.\bigg(\lambda y. \Big(\lambda z. (x\times y + z ) \Big) \bigg)$$

What the author has shown is that you can take a function with many arguments and transform it into many simpler functions with just one argument, the bigger function is just a composition of the simpler ones.

So just how the proof works? In your book the following functions are defined:

\begin{align*} h^\star &= \lambda x . (\lambda y . x − y)\\ h(x,y) &= x-y \end{align*}

You want to show that $h^\star = h$. To do that just take any two arguments $a$ and $b$. First evaluate $h^\star$ in $a$.

$$h^\star(a) = (\lambda x. (\lambda y. x - y))(a) = \lambda y. a - y$$

This gives you a simpler one argument function $h^\prime = h^\star(a)$.

How was $(λy.a−y)(b)=a−b$ concluded

The same way $(\lambda x. (\lambda y. x - y))(a) = \lambda y. a - y$ was concluded. Just evaluate the function in $b$.

$$h^\prime(b) = (h^\star(a))(b) = (\lambda y. a - y)(b) = a - b$$

Which is the same result computed by $h(a,b) = a - b$.

• How in the last line h*(a)(b) = a-b concluded ? Could you elaborate this part ? Feb 18, 2017 at 18:59
• Sorry ..no .. how is (lambda*y .a -y)(b) = a -b ...?Any distribution rule ? Feb 18, 2017 at 19:10
• Beware, this is not a times (multiplication), it's like 'plugging' values in a function argument, so for now think it's something like a textual substitution. The argument is $y$ and the function is $a - y$, so $b$ applied to $\lambda y. a - y$ yields $a-b$ . Feb 18, 2017 at 19:12
• Not a times ? Even with textual substitution I cannot conclude how the last expression came out to be "a-b". Feb 18, 2017 at 19:13
• @AgniveshSingh Btw, if this answer is still not useful to you I can change it to address your problem. Feb 20, 2017 at 20:58